Ảnh hưởng của eWOM trên các phương tiện truyền thông xã hội đến ý định mua sắm – Nghiên cứu tại Thành phố Hồ Chí Minh - Nông Thị Như, Mai (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Based on the combination of the Information Adoption Model (IAM) and the Theory of Reasoned Action (TRA), the study was conducted to investigate the influence of eWOM on social media on purchase intention of consumers. A survey questionnaire of 24 variables was sent to consumers who researched and consulted other consumers on social media before shopping, currently living in Ho Chi Minh City, and being selected under the convenience method. The study used a combination of qualitative and quantitative methods. Data reliability was evaluated by Cronbach's Alpha, EFA exploratory analysis, CFA confirmatory factor analysis, and SEM linear structure model. Research results confirm that Reliability and Quality of information directly positively affect both the usefulness and Acceptance of eWOM. Once consumers have accepted eWOM, they will have more purchase intentions. Concomitantly, the study also proposes some implications to increase purchase intention based on the research results.
Keywords: eWOM; Electronic word of mouth; Social media; Purchase intention